Clinical features of sleep‐related hypermotor epilepsy in relation to the seizure‐onset zone: A review of 135 surgically treated cases. (13th March 2019) - Gibbs, Steve A.; Proserpio, Paola; Francione, Stefano; Mai, Roberto; Cardinale, Francesco; Sartori, Ivana; Castana, Laura; Plazzi, Giuseppe; Tinuper, Paolo; Cossu, Massimo; Russo, Giorgio Lo; Tassi, Laura; et al.
Summary: Objectives: Sleep‐related hypermotor epilepsy (SHE), formerly nocturnal frontal lobe epilepsy, is characterized by abrupt and typically sleep‐related seizures with motor patterns of variable complexity and duration. They seizures arise more frequently in the frontal lobe than in the extrafrontal regions but identifying the seizure onset‐zone (SOZ) may be challenging. In this study, we aimed to describe the clinical features of both frontal and extrafrontal SHE, focusing on ictal semiologic patterns in order to increase diagnostic accuracy. Methods: We retrospectively analyzed the clinical features of patients with drug‐resistant SHE seen in our center for epilepsy surgery. Patients were divided into frontal and extrafrontal SHE (temporal, operculoinsular, and posterior SHE). We classified seizure semiology according to four semiology patterns (SPs): elementary motor signs (SP1), unnatural hypermotor movements (SP2), integrated hypermotor movements (SP3), and gestural behaviors with high emotional content (SP4). Early nonmotor manifestations were also assessed. Results: Our case series consisted of 91 frontal SHE and 44 extrafrontal SHE cases. Frontal and extrafrontal SHE shared many features such as young age at onset, high seizure‐frequency rate, high rate of scalp electroencephalography (EEG) and magnetic resonance imaging (MRI) abnormalities, similar histopathologic substrates, and good postsurgical outcome. Within the frontal lobe, SPs were organized in a posteroanterior gradient (SP1‐4) with respect to the SOZ. In temporal SHE, SP1 was rare and SP3‐4 frequent, whereas in operculoinsular and posterior SHE, SP4 was absent. Nonmotor manifestations were frequent (70%) and some could provide valuable localizing information. Significance: Our study shows that the presence of certain SP and nonmotor manifestations may provide helpful information to localize seizure onset in patients with SHE.